Development and maturation of mango fruits cv. ‘Ubá’ in Visconde do Rio Branco, Minas Gerais State, Brazil - Pereira da Silva, Danielle Fabíola; Chamhum Salomão, Luiz Carlos; Pereira, Laísse Danielle; Dias do Valle, Karminne; Ferreira da Assunção, Hildeu; Cruz, Simério Carlos (Revista Ceres, 2025)
Several criteria have been used to determine fruit maturity, which are based on the appearance and chemical composition of the produce at harvest time. The objective of this study was to evaluate the physical, chemical and physiological changes that occur during the development of mango cv. ‘Ubá’, aiming to determine the stages of fruit development until complete maturation. The experiment was carried out in an approximately 30-year-old orchard in Visconde do Rio Branco, MG (21º00’37"S, 42º50’26"W and 352 m altitude). Weekly, 25 fruits of 15 hoses were collected from the anthesis to the complete maturation in the plant. Samplings took place from August 2007 to January 2008. The characteristics evaluated were length, smaller and larger diameter; CO2 production; color parameters L*, a*, and b* of skin and pulp; fresh and dry mass (fruit, skin, pulp, and seed); solute leakage; pulp firmness; soluble solids (SS); titratable acidity (TA); SS/TA ratio; Vitamin C; carotenoids, starch, and soluble sugars. The development of mango fruit cv. ‘Ubá’ took 23 weeks. The developmental pattern fit a simple sigmoidal model. Fruits attached to the plant reached the respiratory climacteric stage between 20 and 21 weeks after anthesis.